Os batistas em movimento: um estudo da dinâmica sóciorreligiosa de batistas no Brasil: o exemplo de Macaé-RJ - Alvarenga, Leonardo Gonçalves de (2017)
Baptists are Brazil's largest (traditional) evangelical church. The last IBGE census (2010) presented 3,723.853 million members, that is, within the category of "Evangelical Mission" church Baptists have 49%, almost half of evangelical churches. Why have Baptists grown more than other traditional churches? What is the socio-religious dynamic of this grouping and religious denomination? Who are Baptists and what is their relation to tradition? The purpose of this research is to understand, in order to unveil, the plots of the socio-religious dynamics of Baptists within a sociological perspective of religious transmission, taking as a starting point the data of the last four surveys that point both to an atypical growth in relation to other evangelical groups classified by sociology as "traditional" as for a slight numerical deceleration at the turn of the millennium. The socio-religious dynamic of Baptists can be understood from a few moments and key elements: a plurality accentuated by the autonomy of the churches; the priority given to an "aggressive" evangelization, albeit with traces of a strong American civil religion in the mid-twentieth century and in the early years of the second half of the twentieth century; the growth of Pentecostalism as a competitor and strong ally for the growth of Baptists on different fronts; the historical and social moment on which Brazil was going through the process of modernization and urbanization on the rise, as well represented in the case of Macaé-RJ after the installation of Petrobrás in the 1970s; the strategies of entrepreneurial and charismatic leaders, driven by the "imperative of change", which brought to their communities innovations and new means or "ways of believing", less concerned with continuing a "believing line" and more affectionate emotions and bricolages . Therefore, as reading the census numbers, there is nothing that can be called the "Baptist Church" in Brazil, but "Baptist churches" in Brazil